Crucial role of beam spot position in laser assisted plasma arc welding. (February 2014) - Mahrle, A.; Rose, S.; Beyer, E.; Füssel, U.
Abstract : Recently, laser assisted plasma arc welding applying a coaxial arrangement of both heat sources has been developed. This process is now utilised to investigate the impact of beam spot positioning in relation to the arc axis. Arc shapes, arc voltage signals and weld seam geometries for arrangements with a leading and trailing laser beam are compared. The analysis clearly demonstrates the crucial role of small variations in beam spot positioning on the characteristics and the performance of laser assisted plasma arc welding. The results provide new insights into the most efficient driving mechanisms for synergistic effects in laser arc processing.